ANALYSIS OF THE FINANCIAL PERFORMANCES OF COMPANIİES TRADED IN THE BIST ENERGY INDEX (Third Sector Social Economic Review, 2024)
This study aims to evaluate the performance of energy companies listed on Borsa Istanbul (BIST) using an integrated decision-making model and to compare the outcomes. To achieve this, ten accounting-based ratios were selected from the companies' 2022 Balance Sheets and Income Statements. The importance of these ratios was determined using a combination of two weighting methods, SWARA and Entropy. This hybrid approach was designed to provide an objective assessment while also incorporating the subjective evaluations of industry practitioners. Subsequently, the RAFSI method was employed to evaluate and rank the companies' performances. According to the RAFSI ranking—a decision-making approach known for its high consistency and stability—the company with the code A9 (ENJSA) demonstrated the highest performance. Moreover, the analysis revealed that return on equity is the most critical and impactful criterion influencing the performance of energy companies. A comprehensive sensitivity analysis was conducted to test the validity and robustness of the proposed model, and the results confirmed its reliability and stability.
Keywords: BIST; Energy index; SWARA; Entropy; RAFSI; α parametresi; Performance Analysis.